RECHERCHES SUR LES SYSTEMS D’INFORMATION EN UTILISANT L’APL/LAVAL/(RESEARCH ON INFORMATION SYSTEMS USING APL/LAVAL) - Finley, Jr., Marion R. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
See PDF